2018
DOI: 10.14260/jemds/2018/49
|View full text |Cite
|
Sign up to set email alerts
|

Management of Axillary Defect of Hidradenitis Suppurativa Using Keystone Design Islanded Perforator Flap- A Simple and Durable Option

Abstract: BACKGROUND Hidradenitis suppurativa is a chronic cutaneous disease involving recurrent abscesses, fistulating sinus tracts and scarring. The most common sites involved include the axilla, inguinoperineal region and breasts. The disease causes considerable discomfort to the patient due to recurrent abscess and sinus tract with discharge. Medical management will only give temporary relief in resistant disease and surgical excision followed by suitable cover promises a better outcome and hence better quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Among 52 identified, 36 [ 28 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] studies were included, as shown in the corresponding flowchart ( Figure 1 ). We included 286 patients with 380 defects and 387 flaps, some defects being reconstructed by two flaps.…”
Section: Resultsmentioning
confidence: 99%
“…Among 52 identified, 36 [ 28 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] studies were included, as shown in the corresponding flowchart ( Figure 1 ). We included 286 patients with 380 defects and 387 flaps, some defects being reconstructed by two flaps.…”
Section: Resultsmentioning
confidence: 99%